Utilizing Google Sites As An Interactive Platform For Experience Sharing And Collaborative Inquiry Between Students And Teachers (Progress Annals: Journal of Progressive Research, 2025)
Google Sites is a simple and effective tool for creating online spaces where students and teachers can share experiences, ask questions, and learn together. This article explores how the platform can enhance communication and collaboration in education. Through surveys and observations, we found that using Google Sites increased student engagement, improved access to learning materials, and made students more comfortable seeking help. Teachers appreciated the ability to track progress and provide feedback. Overall, Google Sites is a valuable tool for fostering an interactive and supportive learning environment